PEMANFAATAN LIMBAH SAWIT SEBAGAI MEDIA JAMUR MERANG PADA MASYARAKAT DESA CELAWAN - Gustina Siregar; Desi Novita; Sri Utami (Universitas Muhammadiyah Sumatera Utara, 2017)
From the results of the initial survey conducted by the proposing team, the objective to be achieved is to develop an economically independent group of people by providing skills on the cultivation of mushrooms with the media of planting waste oil (empty bunches), providing knowledge about agribusiness opportunities in the future. While the specific targets to be achieved are farmers' groups have the ability to increase productivity of agricultural products, especially mushroom, so it can compete in local and national markets as well as to increase the income of the population per capita. The method to be used is to create demonstration plots and training from teams and resource persons who are experts in the cultivation of mushroom, in order to provide skills to the partners for further monitoring by the proponent team until the partners can develop themselves.At the end of the program the partner has been able to do mushroom cultivation with the production is not optimal (still 30% of the ideal production). It is expected that mushroom cultivation will be carried out by the farmer group continuously with guidance. Skilled farmers make packing and are able to seize opportunities in agribusiness without having to rely on vast land, this is possible because of the demplot as a comparative study for partners.